2022
DOI: 10.1186/s12974-022-02437-7
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell transcriptomics of the ventral posterolateral nucleus-enriched thalamic regions from HSV-1-infected mice reveal a novel microglia/microglia-like transcriptional response

Abstract: Background Microglia participate in the immune response upon central nervous system (CNS) infections. However, the role of these cells during herpes simplex encephalitis (HSE) has not been fully characterized. We sought to identify different microglia/microglia-like cells and describe the potential mechanisms and signaling pathways involved during HSE. Methods The transcriptional response of CD11b+ immune cells, including microglia/microglia-like c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 108 publications
0
9
1
Order By: Relevance
“…PFC-enriched transcripts were enriched for synapse-related pathways. Prkar1a was enriched in PFC microglia, and this transcript has been shown to be elevated in surveillant microglia ( 57 ). Striatal-enriched microglia were associated with microtubule- and cytoskeleton-related pathways.…”
Section: Discussionmentioning
confidence: 99%
“…PFC-enriched transcripts were enriched for synapse-related pathways. Prkar1a was enriched in PFC microglia, and this transcript has been shown to be elevated in surveillant microglia ( 57 ). Striatal-enriched microglia were associated with microtubule- and cytoskeleton-related pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of microglia transcriptomes in the setting of severe HSV1-encephalitis in mice showed they develop a neutrophil-like transcriptional signature, upregulating genes such as resistin-like gamma (Retnlg), retroviral-like aspartic protease, IL-36γ, and C-X-C chemokine receptor 2, while also expressing classical microglial markers P2RY12, transmembrane protein 119 (TMEM119), CSF1R, and Fc receptor-like S (Fcrls). These microglia arise in highly infected brain regions such as the thalamus and most likely represent a direct antiviral response of infected microglial cells [26 ▪ ].…”
Section: Microglia Functions In the Healthy Brainmentioning
confidence: 99%
“…Another study by Uyar et al demonstrated that, depending on the infection levels, microglia are highly phagocytic and participate in antigen presentation (moderately infected thalamic areas) or display impaired physiological functions, such as decreased phagocytic activity (highly infected thalamic regions) [ 47 ]. By using single-cell RNA sequencing (scRNA-seq) on cells isolated from highly infected thalamic regions of HSV-1 infected C57BL/6 mice, Uyar et al revealed a novel transcriptional signature of microglia/microglia-like cells, which they defined as “in transition”.…”
Section: Microglia In Viral Encephalitismentioning
confidence: 99%
“…By using single-cell RNA sequencing (scRNA-seq) on cells isolated from highly infected thalamic regions of HSV-1 infected C57BL/6 mice, Uyar et al revealed a novel transcriptional signature of microglia/microglia-like cells, which they defined as "in transition". Pathway analysis of this cell-type transcriptome showed that "in transition" microglia/microglia-like cells detect the dsRNA of HSV-1 via RIG-I (retinoic acid-inducible gene I, also known as DDX58)/MDA5 in the cytosol), which results in type I IFN production and NLRP3 inflammasome-mediated IL-1β production [47] (Figure 1). Another study by Fekete et al demonstrated a rapid recruitment (within hours) and elimination of HSV-1 infected neurons via microglial P2Y12 receptors in vivo [48].…”
Section: Microglia In Viral Encephalitismentioning
confidence: 99%